2016
DOI: 10.1002/smj.2541
|View full text |Cite
|
Sign up to set email alerts
|

Competitive repertoire complexity: Governance antecedents and performance outcomes

Abstract: Research summary: Past inquiry has found that implementing complex competitive repertoires (i.e., diverse and dynamic arrays of actions) is challenging, but firms benefit from doing so. Our examination of the antecedents and outcomes of complex competitive repertoires develops a more nuanced perspective. Data from 1,168 firms in 204 industries reveal that complexity initially harms performance, but then becomes a positive factor, except at high levels. We use agency and tournament theories, respectively, to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
199
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(208 citation statements)
references
References 111 publications
(226 reference statements)
6
199
0
3
Order By: Relevance
“…Unless the TMT was able to work together, differences in the TMT characteristics and deployment of a large number of various competitive actions would impair firm performance. This was also consistent with Connelly et al (2017) who found that competitive repertoire complexity was harmful to performance in the short term and could overburden the TMT in the long term.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Unless the TMT was able to work together, differences in the TMT characteristics and deployment of a large number of various competitive actions would impair firm performance. This was also consistent with Connelly et al (2017) who found that competitive repertoire complexity was harmful to performance in the short term and could overburden the TMT in the long term.…”
Section: Discussionsupporting
confidence: 90%
“…In this case the range of moves is wide and the actions are not concentrated to any type of actions. Connelly, Tihanyi, Ketchen, Carnes and Ferrier (2017) noted that as competition progresses, organizations find it necessary to engage opponents with a complicated array of moves. This allows the firm to counter an evolving environment in a better manner and gain competitive advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Research on repertoires provides a 'holistic depiction of how characteristics of a firm's body of competitive activity allow it to compete effectively or cause it to struggle in the marketplace' (Connelly et al, 2017(Connelly et al, , p. 1153. From prior work examining a variety of antecedents to competitive repertoires, as well as performance outcomes (Ferrier and Lee, 2002;Gnyawali et al, 2006;Ndofor et al, 2011;Yu et al, 2009), two highly studied attributes of competitive repertoires have emerged: competitive aggressiveness and competitive complexity (Connelly et al, 2017;Ferrier, 2001).…”
Section: Competitive Behaviour and Firm Performancementioning
confidence: 99%
“…Quasi-indexing institutional investors reside somewhere between dedicated and transient investors along these three factors. We focus on ownership by dedicated and transient institutional investors because dedicated investors might use their influence to rein in CEO compensation and transient investors could allow for more lenient compensation policies (Connelly, Tihanyi, Ketchen, Carnes, & Ferrier, 2017). We calculate the percentage of all firm shares held by dedicated and transient investors to measure dedicated institutional ownership and transient institutional ownership.…”
Section: Control Variablesmentioning
confidence: 99%